Clinical interventions to increase vegetable intake in children. Issue 1 (17th February 2023) - Beals, Elizabeth; Deierlein, Andrea; Katzow, Michelle
Abstract : Purpose of review: Eating behaviors and dietary patterns begin in early childhood and persist into adolescence and adulthood, affecting lifelong acute and chronic disease risk. Vegetables provide a high density of necessary vitamins, minerals, and fiber. Dietary intake data show that children of all ages consume below the recommended range for vegetables. Pediatric providers are optimally positioned to promote vegetable intake in childhood. This review seeks to summarize lessons learned from behavioral interventions useful in the pediatric primary care setting to improve vegetable intake. Recent findings: Ten published studies tested behavioral interventions in primary care to increase child vegetable intake. Strategies tested include teaching healthy eating behaviors and role modeling to parents of infants, and motivational interviewing paired with frequent office visits and reminders for families of older children and adolescents. Some strategies suggested positive change, despite study quality being limited by underpowered samples, heterogeneity of outcome measures, and statistical analytic approach. Summary: Increased vegetable intake was achieved in infants through parental role-modeling when providers emphasized healthy dietary choices in parents. Older children increased their vegetable intake with motivational interviewing and frequent reminders from providers. Despite the high prevalence of inadequate vegetable intake among children, at present, there is only a modest body of literature to help guide pediatric providers in implementing practice-based interventions to improve vegetable intake in childhood, highlighting a need for high-quality research in this area.